Eu(III) complex-polymer composite luminescence down-shifting layers for reducing the blue-losses in thin film solar cells. (15th March 2020) - Regalado-Pérez, E.; Mathews, N.R.; Mathew, X.
Graphical abstract: Controlled luminescence properties of Eu(TTA)3 Phen complex in LDS layers enhance the blue response of thin-film solar cells. Highlights: An LDS layer is demonstrated for enhancing blue response in thin-film solar cells. PMMA host matrix is ideal for better distribution of Eu 3+ ions and reduced quenching. Spectral response of CdTe/CdS devices enhanced in the UV region with LDS layer. Abstract: In this work a luminescence down-shifting (LDS) layer, which can reduce significantly the blue-loss due to absorption in the n-type layer of popular thin-film solar cells such as CIGS, CdTe and CZTS is demonstrated. The potential benefits of the developed LDS layer is demonstrated in a prototype CdTe/CdS solar cell. The blue response of the devices coated with Eu(TTA)3 Phen-based LDS layer exhibit an improvement by a factor of two to three times, reaching almost 6% relative enhancement in the short-circuit photocurrent density, compared with the reference device without LDS. The spectral characteristics of the Eu-complex were studied by dissolving in different organic solvents and polymer matrices. The microstructure of the polymer matrix plays a key role on the size, shape and spatial distribution of Eu-complex microparticles, which enables a control of photoluminescence properties at optimal conditions of agglomeration, isotropic luminescence and reduced quenching. The results indicate that the solvents affect differently the spectral characteristics of the emission spectra of the Eu-complex, which show a hypsochromic band shift as the solvent polarity increases. The analysis of the relative intensity ratio (R) of 5 D0 → 7 F2 to 5 D0 → 7 F1 transition indicated the deterioration of local symmetry around europium ions with the reduction of solvent polarity. These results provide a means to improve the emission efficiency of fluorophores embedded in porous matrices and also bring new insights into LDS materials for photovoltaic devices. The developed LDS layer will have applications in devices which use a high band gap heterojunction partner.